Construct validity of a new intermittent aerobic fitness field test in elite soccer players - Benedetti, L.; Prandelli, N.; Aiello, P.; Manari, G.; Nigro, F.; Maracora, S.; Di Michele, R. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: The aim of the study was to evaluate the construct validity of a novel constant-velocity Intermittent Recovery Test (IRT), designed to evaluate aerobic fitness in the field in soccer players.